Association Between A-Waves and Outcome in Pediatric Guillain-Barré Syndrome - Jin, Mei; Liu, Jing; Zhao, Ziwei; Geng, Wenjin; Sun, Suzhen (Frontiers in Neurology, 2022)
Introduction To examine the importance of abundant A-waves in electrophysiological classification and prognosis of pediatric Guillain-Barré Syndrome (GBS). Methods A single-center and retrospective study enrolling 65 children-patients, aged 16 years and younger, with clinically diagnosed GBS between 2013 to 2020. Hughes grade was used to assess functional disability at nadir, 1 month, and 6 months after symptom onset. Patients were divided into 2 groups according to the presence of abundant A-waves. Clinical features and prognosis between the 2 groups were compared. Results The distal motor latency of the median nerve in patients with GBS with A-waves (9.18 ms) was more prolonged than that of patients with GBS without A-waves (4.1 ms). An electrophysiological variant of these two groups was also statistically different (p = 0.006). The short-term prognosis of patients with AIDP with A-waves was worse than patients with AIDP without A-waves (χ2 = 5.022, p = 0.025), and univariable logistic regression analysis showed statistically significant (OR: 5.844, 95% CI 1.118–30.553; p = 0.036). Conclusion A-waves were strongly associated with demyelination and poor short-term prognosis of AIDP in children. We proposed an electrophysiological marker for early prediction of outcome in the AIDP subtype of GBS, applicable for clinical practice and future treatment administration.